New constraints on the 12CO(2–1)/(1–0) line ratio across nearby disc galaxies. Issue 3 (31st March 2021) - den Brok, J S; Chatzigiannakis, D; Bigiel, F; Puschnig, J; Barnes, A T; Leroy, A K; Jiménez-Donaire, M J; Usero, A; Schinnerer, E; Rosolowsky, E; Faesi, C M; Grasha, K; et al.
ABSTRACT: Both the CO(2–1) and CO(1–0) lines are used to trace the mass of molecular gas in galaxies. Translating the molecular gas mass estimates between studies using different lines requires a good understanding of the behaviour of the CO(2–1)-to-CO(1–0) ratio, R 21 . We compare new, high-quality CO(1–0) data from the IRAM 30-m EMIR MultiLine Probe of the ISM Regulating Galaxy Evolution survey to the latest available CO(2–1) maps from HERA CO-Line Extragalactic Survey, Physics at High Angular resolution in Nearby Galaxies-ALMA, and a new IRAM 30-m M51 Large Program. This allows us to measure R 21 across the full star-forming disc of nine nearby, massive, star-forming spiral galaxies at 27 arcsec (∼1–2 kpc) resolution. We find an average R 21 = 0.64 ± 0.09 when we take the luminosity-weighted mean of all individual galaxies. This result is consistent with the mean ratio for disc galaxies that we derive from single-pointing measurements in the literature, R_21, lit = 0.59^+0.18_-0.09 . The ratio shows weak radial variations compared to the point-to-point scatter in the data. In six out of nine targets, the central enhancement in R 21 with respect to the galaxy-wide mean is of order of 10-20 per cent . We estimate an azimuthal scatter of ∼20 per cent in R 21 at fixed galactocentric radius but this measurement is limited by our comparatively coarse resolution of 1.5 kpc. We find mild correlations between R 21 and carbon monoxide (CO) brightness temperature, infrared (IR) intensity, 70–160 µm ratio, and IR-to-CO ratio. All correlations indicate that R 21 increases with gas surface density, star formation rate surface density, and the interstellar radiation field.